PEDAGANG PASAR SENJA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Samosir, Delima; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The title of this research is Dusk Market Traders in Simpang Baru Village, Tampan Sub-district, Pekanbaru City. This research was conducted at Pasar Senja in Simpang Baru Village, Tampan Sub-district, Pekanbaru City. The issues to be studied are as follows: (1) How the characteristics of Dusk Market Traders (2) How the Social Shapes of Capital traders. By taking samples of merchants as many as 48 people. The research method used Simple Random Sampling. Merchant Characteristics can be seen from Gender, Education, Marital Status, Religion, Tribe, Revenue Amount, Merchandise Type, Income Category, and Source of Capital. The forms of social capital in the Senja market that occurs are Relationship of Trust, Social Network, and Norm. Merchant's Social Capital can be seen from the Trust Relationship between fellow traders which consists of a form of trust, the beginning of trust, and the result of trust. Social Network of Merchants to other Senja Market Traders and to agents for cheaper prices consisting of Relationship in Pricing Information and Price Changes to fellow traders to avoid very different price gaps, Payment Transactions of Merchant Goods with Agents, Disaster Visits, Sick Visits, and Happiness Visits. Norms binding on the cooperation such as the absence of written or unwritten rules, but still established a relationship of merchant cooperation with merchants and traders with agents Traders with other Senja Market Traders help each other with mutual benefit For both parties. Keywords: Traders, Senja Market, Social Capital